Mentalising and depression: a mini-review on behavior, neural substrates, and treatment options - Langenbach, Benedikt P.; Koelkebeck, Katja; Knoch, Daria (Frontiers in Psychiatry, 2023)
Major depression is one of the most common mental disorders, affecting millions of people around the globe. In recent years, researchers increasingly investigated social cognition in depression and discovered pronounced alterations. A special focus has been put on mentalising or Theory of Mind, the ability to recognise and understand another person’s thoughts and feelings. While there is behavioural evidence for deficits in this ability in patients with depression as well as specialised therapeutic interventions, the neuroscientific substrates are only beginning to be understood. In this mini-review, we take a social neuroscience perspective to analyse the importance of altered mentalising in depression and whether it can help to understand the origins and perpetuation of the disorder. We will put a special focus on treatment options and corresponding neural changes to identify relevant paths for future (neuroscientific) research.